Pemanfaatan Famili Zingiberaceae Sebagai Obat Tradisional oleh Masyarakat Suku Sasak di Desa Suranadi, Kecamatan Narmada, Kabupaten Lombok Barat - Diah Meidatuzzahra; Rosalina Edy Swandayani (Fakultas MIPA UNM, 2020)
Abstract. One group of plants most used by Indonesians as traditional medicine are plants from the Zingiberaceae family. The aims this study is to assess the level of knowledge and use of the Zingiberaceae family as traditional medicine by the Sasak people in Suranadi Village, Narmada District. This research was conducted using a descriptive exploratory method, which is presented in tabular form. Data collection was carried out by direct observation and semi-structured interviews. Inventory and identification were carried out on the Zingiberaceae family plants found based on observations. Based on the results, it was found that 5 (five) types of medicinal plants in the Zingiberaceae family were used by the Sasak people, namely Jae (Zingiber officinale), Kunyiq (Curcuma longa), Sekoh (Kaempferia galanga), Temu mango (Curcuma amada), Temulawak (Curcuma xanthorrhiza)).Keywords: Zingiberaceae family, traditional medicine, Suranadi village.